HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA MAHASISWA PREKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PALANGKA RAYA - Sibarani, Juliet Valeria; Widayati, Ratna; Mutiasari, Dian (Barigas: Jurnal Riset Mahasiswa, 2023)
Various demands based on competence result in a lot of stress for medical students which is relatively greater when compared to students in other faculties, resulting in frequent stress for the medical students. College students have the potential to experience stress which results in disrupted sleep quality. This study used an analytic observational method with a cross-sectional design. The sample used amounted to 192 respondents. The data were then analyzed using Kendall's Tau with a significance value (<0.05). Sampling was carried out using Simple Random Sampling technique, by looking at the results of data collection using DASS-42 questionnaire to see stress levels and PSQI questionnaire to see sleep quality. The results of this study indicate that of the 192 samples found normal stress levels were 81 (42.2%), mild stress levels 49 (25.5%), moderate stress 35 (18.2%), severe stress 24 (12, 5%), and very severe 3 (1.6%). Meanwhile, the results showed that 176 (91.7%) had poor sleep quality and 16 (8.3%) had good sleep quality. Based on the results of the analysis, it shows that there is a significant relationship between stress levels and sleep quality in preclinic students at the Faculty of Medicine, University of Palangka Raya with a closeness value is in moderate category.